Comprehensive Analysis of Differentially Expressed miRNAs and mRNAs Reveals That miR-181a-5p Plays a Key Role in Diabetic Dermal Fibroblasts - Peng Liu; Yi Zhu; Qin Li; Biao Cheng (Journal of Diabetes Research)
A diabetic nonhealing wound causes heavy economic burden and compromised quality of life in patients. The human dermal fibroblast (HDF), which is an important kind of effector cell in the wound healing process, represents different biological behaviors in the normal and diabetic skins. Given this, we attempt to explore functional changes in diabetic skin-derived HDFs and try to find out the “hub” genes that modulate diabetic HDFs and may be the potential therapeutic targets of diabetic wound healing. We searched the GEO database for related miRNA (GSE68185, GSE84971) and mRNA (GSE49566, GSE78891) profiles. After eliminating batch effects and identifying differentially expressed genes (DEGs), we applied enrichment analyses and found that 3 miRNAs and 30 mRNAs were differentially expressed in diabetic HDFs. Enrichment analyses showed that these genes are closely related to wound healing, for example, extracellular matrix (ECM) organization, angiogenesis, cell proliferation, and migration. Subsequently, we constructed the gene correlation network of DEGs to identify hub genes by merging the protein-protein interaction network, weighted gene coexpression network, and predicted miRNA-mRNA regulatory network. Based on the gene correlation network, we identified the top 3 hub genes: miR-181a-5p, POSTN, and CDH11. Among these, POSTN is a predicted target of miR-181a-5p and is supposed to work together with CDH11 as a functional group. Finally, we verified the expression pattern of the hub genes by in vitro quantification experiments in glucose-cultured HDFs. Our study suggested that miR-181a-5p possibly plays a key role in modulation of HDF behaviors during the diabetic state. However, the effects and mechanisms of miR-181a-5p in high glucose-cultured HDFs remain to be explored in the future.